CENP‐50 is required for papilloma development in the two‐stage skin carcinogenesis model. Issue 8 (6th July 2020) - Saito, Megumi; Kagawa, Naoko; Okumura, Kazuhiro; Munakata, Haruka; Isogai, Eriko; Fukagawa, Tatsuo; Wakabayashi, Yuichi
Abstract: CENP‐50/U is a component of the CENP‐O complex (CENP‐O/P/Q/R/U) and localizes to the centromere throughout the cell cycle. Aberrant expression of CENP‐50/U has been reported in many types of cancers. However, as Cenp‐50/U ‐deficient mice die during early embryogenesis, its functions remain poorly understood in vivo. To investigate the role of Cenp‐50/U in skin carcinogenesis, we generated Cenp‐50/U conditional knockout ( K14Cre ER ‐ Cenp‐50/U fl/fl ) mice and subjected them to the 7, 12‐dimethylbenz(a)anthracene (DMBA)/terephthalic acid (TPA) chemical carcinogenesis protocol. As a result, early‐stage papillomas decreased in Cenp‐50/U ‐deficient mice. In contrast, Cenp‐50/U ‐deficient mice demonstrated almost the same carcinoma incidence as control mice. Furthermore, mRNA expression analysis using DMBA/TPA‐induced papillomas and carcinomas revealed that Cenp‐50/U expression levels in papillomas were significantly higher than in carcinomas. These results suggest that Cenp‐50/U functions mainly in early papilloma development and it has little effect on malignant conversion. Abstract : CENP‐50 is required for papilloma development, but has no function in malignant conversion.